2019
DOI: 10.1186/s12872-019-1167-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the interchangeability of arterial stiffness but not endothelial function parameters in healthy individuals

Abstract: Background Development of instruments capable of detecting early stage vascular disease has increased interest in employing arterial stiffness (e.g. pulse wave velocity (PWV), augmentation index (AIx)) and endothelial dysfunction (e.g. reactive hyperemia index (RHI)) to diagnose atherosclerotic disease before occurrence of a cardiovascular event. However, amongst the equipment designed for this purpose, there is insufficient information regarding each of these parameters to establish appropriate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…This finding is consistent with previous reports among individuals without a history of cardiovascular disease. 43 Linear associations were found between increasing number of risk factors and worsening vascular function (higher PWV and lower RHI) after adjusting for age, sex, and race (Figure 2).…”
Section: Resultsmentioning
confidence: 94%
“…This finding is consistent with previous reports among individuals without a history of cardiovascular disease. 43 Linear associations were found between increasing number of risk factors and worsening vascular function (higher PWV and lower RHI) after adjusting for age, sex, and race (Figure 2).…”
Section: Resultsmentioning
confidence: 94%
“…Consistent with the key role of AS in predicting MACE incidence, carotid pulse wave velocity represents the criterion-standard measure for central AS, and several other noninvasive techniques (eg, photoplethysmography) are available as indicators of specific AS parameters (eg, wave reflections) . While the interchangeability of these measures needs further research, they were found to be independently associated with incident MACE across different subgroups . Therefore, a key unanswered question for public health is the extent to which the adverse effect of depression on MACE might be mitigated by targeting modifiable metabolic mediators.…”
Section: Introductionmentioning
confidence: 99%
“…FMD and EndoPAT™-2000® are not inter-changeable techniques [ 25 ], reflecting macro- and micro-vascular function, respectively. Longitudinal data have demonstrated increased prevalence of hypertension and elevated PWV in impaired FMD [ 26 , 27 ], but contrasting evidence from both healthy and untreated hypertensive individuals shows no association with incident hypertension [ 27 ] or arterial stiffness, and suggests that no excess of microvascular dysfunction exists among otherwise healthy incident hypertensive individuals [ 28 30 ]. Indeed, the hypertensive subgroup demonstrated positive correlation of LnRHI with 24 h SBP, suggesting that the endothelium may demonstrate early compensation in hypertension and arterial stiffening.…”
Section: Discussionmentioning
confidence: 99%